Table of Content - - (Journal of Humanities & Social Sciences, 2025)
Table of Content: 1. Risks of Misuse of Electronic Games on Children and Their Remedies from the Perspective of Islamic Education Ms. Rasha Ahmad Baniismail, Dr. Ayesh Ali Lababneh 2. The Sustainable US Strategy for Leading the International System Asst-Prof. Shadi Sameer Ewadia 3. Spatial Analysis of Land use in Qibah County from 1993 to 2023 Mr. Ahmed Ali Mujalli, Co-Prof. Abdulrahman Suleiman Al-Nosaiyan 4. The Impact of Digital Advertising on Consumer Behavior: An Applied Study on Social Media Users Dr. Sara Saad Al-Dawsari ,Dr. Sadiq Ali Mubarak Al-Shuwaikhat 5. Newlyweds’ Perspectives in Jeddah Towards a Prevention Program Based on the Concept of Differentiation of Self Ms. Musleha Ali Alshomrani, Dr. Yosra Mohammed Bugis 6. Exploring the Symbolism of Nature in the Works of Thomas Hardy: An Eco-critical perspective Dr. Areej Saad Almutairi